Argumenty za nielingwistyczną koncepcją normy. Uwagi dyskusyjne: [Arguments in favour of a nonlinguistic concept of a norm. Some remarks] (Studia Prawnicze / The Legal Studies, 1985)
The present work mainly deals with arguments in favour of a nonlinguistic concept of a norm. The norm is treated as performative but at the same time J. L. Austin’s opinions on performative act are reinterpreted and reviewed.The criticizm of Austin’s opinions reveals, according to the author, the fact that at the first stage of his theory Austin stressed extralinguistic aspects of a performative act. Only at the second stage (separation of an aspect of locution, illocution and perlocution) he recognized their solely linguistic character. According to the author, such a treatment of performatives has been also established in jurisprudence, which leads to paradoxical consequences while considering importance and effectiveness of statements.In view of the above mentioned problems, the author speaks in favour of the opinion that a performative act is not an act of speaking. It is a conventionalized decisive act, thus an act the essential element of which is an act of will, an act having a sense which can be interpreted on the basis of norms. Thus, the author speaks in favour of Austin’s original suggestions.Therefore the author changes his mind as to the character of norms and directives. In his previous works he rather recognized them as linguistic acts, at present he considers them a type of performatives, thus conventionalized decisive acts of will influencing receivers’ behaviour.